347 LONELINESS AMONGST OLDER INPATIENTS IN THE CONTEXT OF COVID-RELATED VISITING RESTRICTIONS. (25th October 2022) - Madden, R; Ahmed, R; Cloonan, J; May, E; Chambers, H; Briggs, R
Abstract: Background: Loneliness can affect people at all stages of life, but appears to be more closely linked to adverse health outcomes such as quality of life and healthcare use amongst older people. There are concerns that restrictions on hospital visits due to infection control policies related to the COVID-19 pandemic may exacerbate loneliness amongst older inpatients. The aim of this study is to quantify the burden of loneliness amongst older inpatients on a specialist geriatric medicine unit. Methods: The study site is a large urban university teaching hospital with a 150-bed specialist geriatric medicine unit, comprising acute medical, rehabilitation and long-stay wards. The University of California, Los Angeles (UCLA) Scale was used to measure symptoms of loneliness with scores≥43 indicating high levels of loneliness. Results: Over 84% of patients were lonely at some time while in hospital, with over one-third (24/76) reporting high levels of loneliness. The mean number of days since last visit from a relative or friend for patients reporting high degrees of loneliness was 11.4 (1.2 – 21.6) days, compared to 5.2 (3.2 – 7.1) days for those with reporting lower levels or no loneliness, though confidence intervals overlapped (p = 0.108). Similarly, patients with higher levels of loneliness had a longer length of stay (68.2 (49.4 – 87.1) compared to 47.9 (33.1 – 62.6) but again findings did not reach significance (p = 0.098). Linear regression models, controlling for competing covariates, found that depressive symptoms, were independently associated with burden of loneliness with a β-Coefficient = 10.69 (5.00 – 16.39). Conclusion: Loneliness is particularly prevalent amongst older inpatients, with a trend towards higher levels of loneliness in those with less frequent visits. Interventions to help older people stay in touch with family and friends, and maintain social connectedness while in hospital, allowing for COVID-related restrictions, would be welcome, particularly for those with longer lengths of stay.